2019
DOI: 10.24953/turkjped.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, diagnosis, and treatment modality of pediatric patients with cystic echinococcosis: a single centre experience

Abstract: Cystic echinococcosis (CE) is among the most common zoonotic infections worldwide. Studies about CE are limited in childhood. The aim of this study was to evaluate clinical, radiological and laboratory characteristics of childhood CE at a tertiary care pediatric hospital. Medical records of children with CE were analyzed between January 2005 and January 2015. A total of 130 patients with a median age of 10.4 years (IQR= 7.2-years-13.2 years) were evaluated. The anatomic locations of cysts were as follows; live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…Results of the present study suggest that exposure to the parasite starts from childhood, and the rate of hospitalization may increase with age. Similar to our findings, Dashti et al [12], Çelebi et al [45], and Kaman et al [46] reported the mean ages of children with CE to be 11.5 ± 6.1 years, 12.4 years, and 10.3 ± 3.5 years, respectively. More than half of our study participants were registered as children aged 11-17 years.…”
Section: Discussionsupporting
confidence: 92%
“…Results of the present study suggest that exposure to the parasite starts from childhood, and the rate of hospitalization may increase with age. Similar to our findings, Dashti et al [12], Çelebi et al [45], and Kaman et al [46] reported the mean ages of children with CE to be 11.5 ± 6.1 years, 12.4 years, and 10.3 ± 3.5 years, respectively. More than half of our study participants were registered as children aged 11-17 years.…”
Section: Discussionsupporting
confidence: 92%
“…[24] IHA test positivity in combination with abdominal ultrasonography is useful in diagnosing liver hydatid cyst, but thoracic CT is usually required to diagnose hydatid cyst of the lung. [25] In our study, echinococcus IHA was positive in 42.9% of the children. Eosinophilia was reported in 20-34% of hydatid cyst cases.…”
Section: Discussionsupporting
confidence: 48%
“…Studies have also been reported the prevalence of the multiorgan involvement in the paediatric patients as 0%-12.5%. [6][7][8][9][10][11][12] In the literature, paediatric patients with the multiorgan involvement have been reported as case reports. [13][14][15][16][17][18][19][20][21][22][23] All the current cases of multiorgan involvement are presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, ≥3 organ involvement is very rare, especially in the paediatric patients. Studies have also been reported the prevalence of the multiorgan involvement in the paediatric patients as 0%–12.5% 6–12 . In the literature, paediatric patients with the multiorgan involvement have been reported as case reports 13–23 .…”
Section: Discussionmentioning
confidence: 99%